Revealing the Numeracy Skills of Eighth-Grade Students in Solving PISA 2022 Quantity Content Problem - Jihan Adi Pradypta; Duano Sapta Nusantara; Ranisa Junita; Florante P Ibarra (Edumatika, 2025)
This study is qualitative descriptive research that aims to describe eighth-grade students’ numeracy skills in solving a PISA 2022 quantity content problem. This focus is important because PISA-type tasks require reasoning, quantitative interpretation, and decision-making skills that are essential for students’ mathematical literacy in real-life situations. Thirty-two eighth-grade students of a junior high school in Jambi, Indonesia, participated in this study. Data were collected through a written test adapted from the PISA 2022 released items and follow-up interviews with selected students. The results showed that most students demonstrated low numeracy performance, particularly in interpreting information, performing multi-step calculations, and drawing correct conclusions. Only a small number of students were able to meet the expected indicators of numeracy skills. These findings indicate that students have not yet fully met the cognitive demands of PISA quantity tasks. The results highlight the need for instruction that provides more opportunities for students to practice contextual quantitative reasoning. For classroom practice, teachers are encouraged to incorporate multi-step contextual tasks that gradually strengthen students’ interpretation, strategy selection, and reasoning abilities. The findings also serve as a basis for further research on developing PISA-type jumping tasks adapted to relevant local contexts to support students’ numeracy skills.